2009
DOI: 10.1158/1078-0432.ccr-09-1631
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Paraffin-Embedded Primary Melanoma Using the DASL Assay Identifies Increased Osteopontin Expression as Predictive of Reduced Relapse-Free Survival

Abstract: Purpose Gene expression studies in melanoma have been few because tumors are small and cryopreservation is rarely possible. The purpose of this study was to evaluate the Illumina DASL Array Human Cancer Panel for gene expression studies in formalin-fixed melanoma primary tumors, and to identify prognostic biomarkers. Experimental Design Primary tumors from two studies were sampled using a tissue microarray needle. Study 1: 254 tumors from a melanoma cohort recruited 2000-2006. Study 2: 218 tumors from a case… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 38 publications
5
98
1
Order By: Relevance
“…Previous studies have reported that increased OPN mRNA expression is associated with unfavourable patient prognosis in human cancers, including melanoma [9,29]. In addition, we extended our studies to OPN protein levels and therefore fabricated tissue microarray platforms for 93 primary melanomas.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies have reported that increased OPN mRNA expression is associated with unfavourable patient prognosis in human cancers, including melanoma [9,29]. In addition, we extended our studies to OPN protein levels and therefore fabricated tissue microarray platforms for 93 primary melanomas.…”
Section: Discussionmentioning
confidence: 92%
“…In human malignant melanoma, OPN expression is significantly associated with reduced relapse-free survival and additional histological parameters that are associated with poor clinical outcome [7,24,29,33]. OPN is a prognostic marker in a variety of cancers [30,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly pigmented specimens were avoided due to previously published technical issues that reported low RNA yield in the presence of abundant melanin. 19 A total of 22 samples were screened; however, only 19 samples were used, 3 being excluded on the basis of poor RNA quality. In all, 10 primary melanomas and 9 sentinel lymph node metastases were evaluated, including 4 autologous pairs of primary melanoma and sentinel lymph node metastasis (from 4 patients).…”
Section: Case Selection and Sample Collectionmentioning
confidence: 99%
“…Others, using cell lines or tissue samples, have studied DNA expression profiling of normal melanocytes, nevi, primary melanomas, and regional and distant metastases. [7][8][9][10][11][12][13][14][15][16][17][18][19] Conway et al 19 used the cDNA-mediated annealing, selection, extension, and ligation assay to evaluate formalin-fixed, paraffin-embedded archival primary melanoma specimens, and reported osteopontin overexpression as a potential prognostic biomarker. Rangel et al, 20 using immunohistochemistry, had previously shown that overexpression of osteopontin, correlated with the likelihood of sentinel lymph node metastasis.…”
mentioning
confidence: 99%